Gene Structures, Classification, and Expression Models of the DREB Transcription Factor Subfamily in Populus trichocarpa - Yunlin Chen; Jingli Yang; Zhanchao Wang; Haizhen Zhang; Xuliang Mao; Chenghao Li (The Scientific World Journal)
We identified 75 dehydration-responsive element-binding (DREB) protein genes in Populus trichocarpa. We analyzed gene structures, phylogenies, domain duplications, genome localizations, and expression profiles. The phylogenic construction suggests that the PtrDREB gene subfamily can be classified broadly into six subtypes (DREB A-1 to A-6) in Populus. The chromosomal localizations of the PtrDREB genes indicated 18 segmental duplication events involving 36 genes and six redundant PtrDREB genes were involved in tandem duplication events. There were fewer introns in the PtrDREB subfamily. The motif composition of PtrDREB was highly conserved in the same subtype. We investigated expression profiles of this gene subfamily from different tissues and/or developmental stages. Sixteen genes present in the digital expression analysis had high levels of transcript accumulation. The microarray results suggest that 18 genes were upregulated. We further examined the stress responsiveness of 15 genes by qRT-PCR. A digital northern analysis showed that the PtrDREB17, 18, and 32 genes were highly induced in leaves under cold stress, and the same expression trends were shown by qRT-PCR. Taken together, these observations may lay the foundation for future functional analyses to unravel the biological roles of Populus’ DREB genes.